Studies of the Major Gene Expression and Related Metabolites in Cannabinoids Biosynthesis Pathway Influenced by Ascorbic Acid - Soltan, Keyvan; Dadkhah, Behnoush (Planta Medica International Open, 2022)
Cannabis sativa L. is an annual dioecious plant that belongs to the Cannabaceae family and is essential for different pharmaceutical and nutritional properties. The most important and prevalent cannabinoids in cannabis are cannabidiol and delta-9-tetrahydrocannabinol. The application of elicitors is an effective method to improve secondary metabolite production, leading to a whole spectrum of molecular, genetic, and physiological modifications. Therefore, the expression changes of four key genes (THCAS, CBDAS, PT, and OLS) of the cannabinoids pathway along with the delta-9-tetrahydrocannabinol and cannabidiol metabolites fluctuation were surveyed following the application of ascorbic acid as an elicitor. Cannabis was sprayed immediately before flowering with ascorbic acid. Treated and untreated (control) plants were sampled in different time courses for real-time PCR and HPLC experiments. Results showed significant increases in THCAS, CBDAS, PT, and OLS expression after ascorbic acid treatments. The results of metabolite quantification also indicated that secondary metabolites, especially delta-9-tetrahydrocannabinol and cannabidiol, increased after the ascorbic acid application. This study contributes to the growing body of knowledge of the functions of key genes in the cannabinoids pathway to the engineering of cannabis for improving the production of delta-9-tetrahydrocannabinol and cannabidiol metabolites in this plant.
Keywords: Cannabis sativa; Cannabaceae; ascorbic acid; cannabidiol; delta-9-tetrahydrocannabinol; gene expression; metabolites